An Innovative Directional Blasting Technique for Coal Mine Exploration and Engineering Testing. (22nd July 2022) - Gao, Rui; Jiang, Ze; Lan, Bo; Lin, Yongqing; Dai, Xianglin
Abstract : Blasting is a key method of controlling large-area hanging roofs and strong mine pressure in coal mine. The crack propagation direction after blasting has a decisive influence on control effect, and the existing blasting techniques have poor directionality, making it difficult to form a continuous, precise crack. A compound blasting technique (CBT) was proposed; this could achieve a precision, directional crack by using the combination of perforating bullet and explosives, with perforating bullet detonation first and then explosive blasting. The principle of directional crack formation by CBT was studied and a complete set of equipment was introduced, and the effect of continuous directional crack forming was studied experimentally. A CBT test was conducted in Tashan coal mine (Datong mining area): the results showed that a single crack surface was formed in the borehole after the compound blasting, which indicated the desired blasting effect. The CBT improves the accuracy and controllability of fractures and realizes precise directional control of rock strata.